(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2025)
Diabetes mellitus (DM) is commonly diagnosed by monitoring blood glucose levels; however, this method is invasive and may cause infection at the puncture site. As a non-invasive alternative, urine-based glucose monitoring has gained attention. This study investigates the effect of zinc oxide (ZnO) incorporation on the performance of a waveguide-based glucose sensor utilizing evanescent wave absorption. Two waveguides were fabricated using recycled polystyrene waste as the core material, with ZnO added to one of the samples. The sensitivity and thermal stability of both sensors were characterized and compared to evaluate ZnO’s impact. Experimental results demonstrate that the ZnO-enhanced waveguide exhibits significantly improved performance, achieving a sensitivity of 9×10⁻⁵ V/ppm, a correlation coefficient of 99.12%, a linear detection range of 0-1000 ppm, and enhanced thermal stability. These findings indicate that the ZnO-integrated waveguide sensor offers strong potential as a low-cost, non-invasive alternative for early DM detection via urine analysis.